The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/cid/ciaa977
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Dynamics and Determinants of Severe Acute Respiratory Syndrome Coronavirus 2 Transmissions Among Healthcare Workers of Adult and Pediatric Settings in Central Paris

Abstract: Background Health-care workers (HCW) have paid a heavy toll to the coronavirus disease-19 (COVID-19) outbreak. Routes of transmission remain to be fully understood. Methods This prospective study compared a 1,500-bed adult and a 600-bed pediatric setting of a tertiary-care university hospital located in central Paris. From February 24th until April 10th, 2020, all symptomatic HCW were screened for severe acute respiratory syn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…A recent study from a pediatric hospital in Chicago, revealed a low (1%‒2%) prevalence of SARS-CoV-2 among children without COVID-19 symptoms as well as no secondary transmission among HCWs exposed to those patients [ 14 ]. Another study, comparing the dynamics and determinants of SARS-CoV-2 transmissions among HCWs of adult and pediatric settings in Paris, revealed a significantly lower attack rate in a pediatric setting (2.3% vs 3.2%, respectively) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from a pediatric hospital in Chicago, revealed a low (1%‒2%) prevalence of SARS-CoV-2 among children without COVID-19 symptoms as well as no secondary transmission among HCWs exposed to those patients [ 14 ]. Another study, comparing the dynamics and determinants of SARS-CoV-2 transmissions among HCWs of adult and pediatric settings in Paris, revealed a significantly lower attack rate in a pediatric setting (2.3% vs 3.2%, respectively) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in the 3.4% to 11.2% range described in other European surveys [10][11][12][13][14]. We estimated that the prevalence (inverse variance method with random effect) among French healthcare workers was 12.0% (CI 95, 7.0% to 19.0%), varying by the sampling method, and ranging from 7.0% when considering any healthcare workers to 12% among frontline caregivers, and 31.0% among symptomatic health professionals (Appendix D) [3,5,[15][16][17][18]. Such a variation in estimation highlights the need to identify subgroups at higher risk of infection.…”
Section: Discussionmentioning
confidence: 79%
“…Yet, the prevalence of the infection, including asymptomatic forms, in French healthcare workers remains poorly known. In small-sized studies, it was ranging from 2.2% in serologic screening among asymptomatic healthcare workers to 28% in RT-PCR among symptomatic healthcare workers [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The recent study from pediatric hospital in Chicago, revealed a low (1-2 %) prevalence of SARS-CoV-2 among children without COVID-19 symptoms as well as no secondary transmission among HCWs exposed to these patients [14]. Another study, comparing dynamics and determinants of SARS-CoV-2 transmissions among HCWs of adult and pediatric settings in Paris, revealed significantly lower attack rate in the pediatric setting (2.3% vs 3.2%, respectively) [15].…”
Section: Discussionmentioning
confidence: 99%